2021
DOI: 10.1137/19m1274316
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearizing Two-parameter Eigenvalue Problems

Abstract: We investigate a technique to transform a linear two-parameter eigenvalue problem into a nonlinear eigenvalue problem (NEP). The transformation stems from an elimination of one of the equations in the two-parameter eigenvalue problem, by considering it as a (standard) generalized eigenvalue problem. We characterize the equivalence between the original and the nonlinearized problem theoretically and show how to use the transformation computationally. Special cases of the transformation can be interpreted as a r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Thus, nonlinearization technique works if a solution to 2PEP corresponds to a simple eigenvalue a 2 of the GEP represented by the equation (4.1). Again, in [33] it is also showed that the Jacobian J(a 1 , a 2 ) is nonsingualar if we take the simple eigenvalue a 1 of the GEP such that s is not orthogonal to the corresponding eigenvector, which confirms the existence of nonlinerization. Therefore, the nonlinearization exists simple eigenvalues of GEP given in equation (4.1).…”
Section: Equivalence and Existence Of Nonlinearization Of The 2pepmentioning
confidence: 84%
See 4 more Smart Citations
“…Thus, nonlinearization technique works if a solution to 2PEP corresponds to a simple eigenvalue a 2 of the GEP represented by the equation (4.1). Again, in [33] it is also showed that the Jacobian J(a 1 , a 2 ) is nonsingualar if we take the simple eigenvalue a 1 of the GEP such that s is not orthogonal to the corresponding eigenvector, which confirms the existence of nonlinerization. Therefore, the nonlinearization exists simple eigenvalues of GEP given in equation (4.1).…”
Section: Equivalence and Existence Of Nonlinearization Of The 2pepmentioning
confidence: 84%
“…But it is singular in non generic situation only. In [33], Ringh and Jarlebring showed that the Jacobian J(a 1 , a 2 ) is singular if and only if the GEP (4.1) has at least Jordan chain of length two or more. Thus, nonlinearization technique works if a solution to 2PEP corresponds to a simple eigenvalue a 2 of the GEP represented by the equation (4.1).…”
Section: Equivalence and Existence Of Nonlinearization Of The 2pepmentioning
confidence: 99%
See 3 more Smart Citations